Technological applications of luminescent, colorimetric and absorption based sensors. - Stephen Robert Ricketts (2009)
This thesis deals with the development of luminescent, absorbance based, and colorimetric sensors for a variety of technological applications including pressure sensitive paints, sensors for the preservation of artefacts for the British museum and sensors for the measurement of dissolved carbon dioxide and oxygen in blood. Throughout this thesis it can be seen that these sensors have significant advantages over traditional sensors. Chapter 3 describes the development of colorimetric oxygen sensors for the detection of leaks in display cases specifically developed for the British Museum. The technological challenges facing the development of these sensors such as means of illumination and photodegradation are assessed and solutions to these problems are sought. Chapter 4 sees the development of a novel temperature corrected pressure sensitive paint. Utilising a luminescent colorimetric oxygen sensor and an absorption based temperature sensor together in the same sensor. The colour response of the absorption based temperature layer viewed under white light enables temperature corrections to be made to the response of the luminescent colorimetric oxygen sensor which can be viewed under UV light. Chapter 5 describes the development of a new type of colorimetric oxygen sensor, which uses a green LED as a source of both excitation and emission, replacing the green lumophores used in two lumophore colorimetric sensors. The work discussed in Chapter 6 describes the design of luminescent based sensors for the measurement of oxygen and carbon dioxide in blood, such as might be required to monitor the performance of an artificial lung. The development and design of a combined complete compact sensor, comprising: excitation source, sensor element, and detector. The sensors measure oxygen and carbon dioxide in blood and water with an inline response to changing concentrations of these gases from partial pressures of 0-100 kPa for oxygen and 0-40 kPa for carbon dioxide within the range of clinical interest.